The Role of Germany, Italy and Portugal in the Spanish Civil War (1936-1939) in the Representation of the British Media - Malay, Vera V.; Fomichev, Nickolay N.; Timoshkova, Olga A.; Uryvsky, Andrew P.; Orehova, Marina S. (International Journal of Criminology and Sociology, 2022)
The purpose of the article is to reveal the nature of the reflection of the events of the Spanish Civil War of 1936-1939 in the British press. The most important factor shaping public opinion was the periodical press. The authors emphasize that events on the European continent, including local conflicts, significantly influenced the mindset of British society, combined with an acute party struggle on foreign policy issues. The practical component of the article is based on the analysis of about 20 titles of British Newspapers political orientation. The results of the study showed that the publications were divided on the issue of criticism or support for the Italian-German intervention in Spain as follows: sharp rejection - the Communist, labour and liberal press (violation of international norms, understanding of intervention as aggression); neutral or slightly negative attitude: part of the conservative press (mutual internationalization of the conflict).